CROSS-SYSTEM ANALYSIS OF QUEUEING SYSTEMS INTERACTIONS IN DISTRIBUTED NETWORKS - Муханов, Самат; Дарын, Амрин; Жакыпбеков, Сырым (МЕЖДУНАРОДНЫЙ ЖУРНАЛ ИНФОРМАЦИОННЫХ И КОММУНИКАЦИОННЫХ ТЕХНОЛОГИЙ, 2025)
The increasing reliance on cloud computing has brought both remarkable opportunities and complex challenges. Distributed networks, such as cloud computing environments, are inherently dynamic and require robust systems to handle varying workloads efficiently. This study explores the intricate interactions between multiple queueing models within these systems, providing a fresh perspective on their impact on performance. By using queueing theory, we delve into key metrics like response time, system throughput, and resource allocation strategies. The authors’ analysis highlights the advantages of horizontal and vertical scaling, container orchestration, and the critical role of network bandwidth and latency in optimizing cloud infrastructure performance. The researchers also examines how queueing behaviors affect service-level agreements (SLAs), system availability, fault tolerance, and energy efficiency. The integration of analytical and simulation-based approaches enables to evaluate real-world scenarios and identify performance bottlenecks. The findings not only demonstrate the practical applications of queueing theory but also emphasize its relevance in managing resource contention and improving elasticity in multi-tenant environments. This research lays the groundwork for future development of predictive and adaptive models, contributing to the design of smarter, more scalable, and resilient cloud-based systems.